Treatment patterns and frequency of key outcomes in acute severe asthma in children: a Paediatric Research in Emergency Departments International Collaborative (PREDICT) multicentre cohort study. Issue 1 (17th March 2022) - Craig, Simon; Powell, Colin V E; Nixon, Gillian M; Oakley, Ed; Hort, Jason; Armstrong, David S; Ranganathan, Sarath; Kochar, Amit; Wilson, Catherine; George, Shane; Phillips, Natalie; Furyk, Jeremy; et al.
Abstract : Rationale: Severe acute paediatric asthma may require treatment escalation beyond systemic corticosteroids, inhaled bronchodilators and low-flow oxygen. Current large asthma datasets report parenteral therapy only. Objectives: To identify the use and type of escalation of treatment in children presenting to hospital with acute severe asthma. Methods: Retrospective cohort study of children with an emergency department diagnosis of asthma or wheeze at 18 Australian and New Zealand hospitals. The main outcomes were use and type of escalation treatment (defined as any of intensive care unit admission, nebulised magnesium, respiratory support or parenteral bronchodilator treatment) and hospital length of stay (LOS). Measurements and main results: Of 14 029 children (median age 3 (IQR 1–3) years; 62.9% male), 1020 (7.3%, 95% CI 6.9% to 7.7%) had treatment escalation. Children with treatment escalation had a longer LOS (44.2 hours, IQR 27.3–63.2 hours) than children without escalation 6.7 hours, IQR 3.5–16.3 hours; p<0.001). The most common treatment escalations were respiratory support alone (400; 2.9%, 95% CI 2.6% to 3.1%), parenteral bronchodilator treatment alone (380; 2.7%, 95% CI 2.5% to 3.0%) and both respiratory support and parenteral bronchodilator treatment (209; 1.5%, 95% CI 1.3% to 1.7%). Respiratory support was predominantly nasal high-flow therapy (99.0%). The most common intravenous medication regimens were: magnesium alone (50.4%), magnesium and aminophylline (24.6%) and magnesium and salbutamol (10.0%). Conclusions: Overall, 7.3% children with acute severe asthma received some form of escalated treatment, with 4.2% receiving parenteral bronchodilators and 4.3% respiratory support. There is wide variation treatment escalation.